Perbedaan asupan zat gizi, pengetahuan anemia, dan kepatuhan konsumsi Tablet Tambah Darah (TTD) pada remaja putri di pesantren dan nonpesantren - Esya Aqilla Alfianti; Fillah Fithra Dieny; Dewi Marfu’ah Kurniawati; Hartanti Sandi Wijayanti (Jurnal Gizi Klinik Indonesia)
Differences in nutrient intake, anemia knowledge, and adherence to blood supplement tablet consumption between adolescent girls in Islamic boarding schools and non-Islamic boarding schools